Public Relations dan Community Engagement dalam Mempromosikan Wisata Konservasi Penyu di Serangan, Denpasar Selatan - Septiana, Ni Putu Devi; Yanti, Ni Kadek Winda (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: This study aims to analyze the role of public relations (PR) strategies and Community Engagement in promoting turtle conservation tourism at the Turtle Conservation and Education Center (TCEC) in Serangan, South Denpasar. Research methods: The study employed a qualitative descriptive approach using observation, in-depth interviews, and documentation. The research involved TCEC managers, local communities, tourists, and related stakeholders to obtain comprehensive insights into communication practices and community involvement. Findings: The implementation of the Two-Way Symmetrical Communication model by the existing PR practitioner effectively established mutual communication between the conservation institution and the surrounding community. The active participation of local residents in educational programs, digital promotions, and conservation activities significantly increased public environmental awareness and improved TCEC’s image as a sustainable tourism destination. Implication: This study highlights the importance of synergizing communication strategies with community participation to support conservation-based tourism promotion and environmental education.